High-yield synthesis of gold nanoribbons by using binary surfactants. Issue 7 (18th December 2014) - Xu, Yong; Wang, Xuchun; Chen, Lei; Zhao, Yang; He, Liu; Yang, Peipei; Wu, Haihua; Bao, Feng; Zhang, Qiao
Abstract : Gold nanoribbons with high morphological yield and great SERS performance have been successfully prepared by using binary surfactants. Abstract : In this Communication, we report a seeded growth protocol for the synthesis of gold nanoribbons with high morphological yield by using a binary surfactant system. The detailed formation process and the potential SERS application of gold nanoribbons have been systematically investigated.